Long-term environmental monitoring for preventive conservation of external historical plasterworks. (15th April 2022) - Torres-González, Marta; Rubio-Bellido, Carlos; Bienvenido-Huertas, David; Alducin-Ochoa, J.M.; Flores-Alés, V.
Abstract: In this study, an analysis of the environmental conditions in a Csa climatic zone for the conservation of plasterwork of the Real Alcázar of Seville is carried out. The measurements obtained from in-situ monitoring are compared with the measurements provided by AEMET (State Meteorological Agency in Spain) during the reference year and the study is completed by estimating future environmental conditions using two alternative approaches: a morphing process from the EPW of the climatic zone and the application of M5P data mining algorithms. An optimal temperature range is established for the conservation of the plasterwork that prevents their dehydration or the freezing of water particles contained. The transformation of gypsum into bassanite, the risks associated with exposures to high relative humidity and the consequences of the slight hygroscopicity of the material and the environmental conditions that must be developed to favor the growth of mold on the surface or the cracking of polychromies that embellish these plaster decorations on numerous occasions are analyzed. The results obtained allow us to establish preventive conservation measures not only on the plasterwork but also on the Real Alcázar of Seville and that architectural heritage located in the subtropical dry-summer climate. Highlights: The influence of temperature and relative humidity in the preservation of plasterwork. Comparative analysis between different approaches. Climate change will affect the maintenance of materials. Future estimations allow to establish mitigation actions on architectural heritage.